Diagnostic histopathological features distinguishing palmoplantar pustulosis from pompholyx. Issue 5 (28th March 2019) - Masuda‐Kuroki, Kana; Murakami, Masamoto; Kishibe, Mari; Kobayashi, Satomi; Okubo, Yukari; Yamamoto, Toshiyuki; Terui, Tadashi; Sayama, Koji
Abstract: Palmoplantar pustulosis (PPP) and pompholyx are both chronic and relapsing diseases occurring on the palms and soles. Although these two diseases have been considered completely different from each other, it is sometimes very difficult even for dermatologists to differentiate them from each other because of their similarities in clinical presentation. In this study, we aimed to analyze the histopathological features of PPP and pompholyx and find out "clues" to differentiate between PPP and pompholyx by their histopathological features. The histopathology of 11 PPP and six pompholyx patients, who were diagnosed with typical clinical history and histopathology, were carefully observed. PPP cases were divided into three phases (vesicle, pustulovesicule and pustule) and pompholyx cases were divided into two phases (vesicle and pustule), and histopathological findings and a 4‐point checklist to distinguish between PPP and pompholyx were preliminarily established. To confirm whether the checklist establishes the clues for diagnosis, biopsy samples from 43 patients (32 PPP and 11 pompholyx) who had been already diagnosed at five hospitals were examined according to our checklist without any additional clinical information. According to our 4‐point checklist, 31 of 32 PPP patients and all 11 pompholyx patients were diagnosed histopathologically consistent with their clinical diagnosis. In conclusion, histopathological findings of "vesicles without spongiosis" and "microabscess on the edges of vesicles" would be impact points for the differential diagnosis between PPP and pompholyx. The 4‐point checklist was trustworthy to distinguish between PPP and pompholyx.